The The Effect of Education on Medication Adherence And Dietary Behaviour in Type II Diabetes Mellitus Patients - Purnamawati, Dessy; Suyanto, Suyanto (Journal of Smart Nursing and Health Science, 2026)
Background: Type II diabetes mellitus is a chronic disease with an increasing incidence rate and the potential to cause various complications if not managed properly. Medication adherence and dietary behaviour are important aspects of diabetes control, but many patients still do not optimally adhere to them. Health education is one of the main pillars of diabetes management because it plays a role in increasing knowledge and shaping patient behaviour. This study aims to determine the effect of education on medication adherence and dietary behaviour in patients with type II diabetes mellitus. Methods: This study used a quasi-experimental design with a one-group pretest–posttest approach. The study sample consisted of 52 patients with type II diabetes mellitus who were selected using purposive sampling. The intervention took the form of health education provided to respondents on understanding diabetes, treatment, and proper diet management. Medication adherence and dietary behaviour were measured before and after the education using a standardised questionnaire. Results: The results showed an increase in medication adherence and improvement in dietary behaviour after the education. Health education was proven to encourage changes in patient behaviour in managing their disease more optimally. Conclusion: The conclusion of this study indicates that education has a positive effect on increasing medication adherence and dietary behaviour in type II diabetes mellitus patients, so education needs to be integrated continuously into nursing services